2020
DOI: 10.15557/pimr.2020.0062
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal undifferentiated carcinoma – a rare cause of proptosis in elderly

Abstract: Sinonasal undifferentiated carcinoma is a rare and extremely aggressive sinonasal tract malignancy. It is a rapidly enlarging tumour and a highly destructive lesion. We hereby report a 71-year-old Malay male with progressive left proptosis for one month, associated with reduced vision in the left eye, intermittent diplopia and anosmia. He was later diagnosed as having sinonasal undifferentiated carcinoma. The patient subsequently underwent a series of radiotherapy and showed improvement following treatment. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The most common presenting symptoms of patients with SNUC include nasal obstruction, epistaxis, and facial pain, which were described in the previous studies [ 11 , 12 ]. A study by Xu et al showed 85% of patients were diagnosed with Stage IV SNUC during presentation due to symptoms similar to benign sinus disease [ 13 ].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The most common presenting symptoms of patients with SNUC include nasal obstruction, epistaxis, and facial pain, which were described in the previous studies [ 11 , 12 ]. A study by Xu et al showed 85% of patients were diagnosed with Stage IV SNUC during presentation due to symptoms similar to benign sinus disease [ 13 ].…”
Section: Discussionmentioning
confidence: 92%
“…Immunohistochemical analysis of SNUC showed simple epithelial type cytokeratin (CK7, CK8, CK17) and EMA with variable reactivity towards neuro-specific enolase (NSE), tumor marker p53, chromogranin, and synaptophysin. This test is very helpful to discern SNUC from other undifferentiated malignancies, such as olfactory neuroblastoma and undifferentiated nasopharyngeal carcinoma [ 11 ].…”
Section: Discussionmentioning
confidence: 99%